Implementation of Rational Emotive Behavior Therapy (REBT) Techniques to Improve Students' Adaptation Skills - Faiza Maulida; Wanty Khaira (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: The ability to adapt for students in facing various demands of academic, social, and emotional development in the school environment. Inability to adapt can have a negative impact on students' learning achievement and psychological well-being. Thus, appropriate psychological intervention is needed to help students develop this ability. The Rational Emotive Behavior Therapy (REBT) approach is a view based on humans, which explains that individuals have a tendency to think irrationally one of which is obtained through social learning. Rational Emotive Behavior Therapy (REBT) aims to eliminate emotional disorders that can damage the individual such as anxiety, hatred, fear, troubled feelings, anger, and so on. Aim: This study aims to test the effectiveness of group counseling services based on Rational Emotive Behavior Therapy (REBT) in improving students' self-adjustment abilities at MTsN 2 Aceh Besar. Using a quantitative approach with a pre-experimental one group pre-test and post-test design, the study sample consisted of 7 students selected through a purposive sampling technique based on the results of the self-adjustment questionnaire. Result and Discussions: The research instrument was a self-adjustment questionnaire that had been tested for validity and reliability. The results of data analysis showed that the average score of students' self-adjustment increased from 194.71 in the pre-test to 236.71 in the post-test. The paired sample t-test showed a significance value of 0.001 (<0.05), indicating a significant difference between the scores before and after the intervention. These findings prove that REBT-based group counseling services are effective in improving students' self-adjustment abilities, including emotional, intellectual, social, and responsibility aspects.